E-examination and academic performance of biology students in Akwa Ibom State College of Education, Afaha Nsit- Nigeria - Agnes Lambert; Paulinus Etim (Global Econedu, 2022)
Abstract This study investigated the effect of e-examination on Biology students’ academic performance in Akwa Ibom State College of Education, Afaha Nsit. A quasi-experimental research design was adopted to study a sample size of 165 out of 408 first Year Biology (NCE 1) students in 2015/2016 academic session. Two research questions and two null hypotheses guided the study. While two research instruments namely: Computer Appreciation Test (CAT) and Biology Performance Test (BIOPET) were used for data collection. Whereas Mean was used in answering the research questions, t-test statistical technique was used to test the hypotheses at .05 level of significance. Major findings revealed that there was significant effect of writing examination electronically on students’ academic performance; and that no statistical difference existed between male and female students’ performance who wrote exam electronically. Subsequent upon these findings, it is recommended amongst others that students of the Institution should be introduced to the electronic mode of writing examinations through series of tutorials and hands-on experience in order to create more familiarization as the electronic mode of exam writing is gradually coming to stay in Nigerian tertiary education system.